Initial pore pressures under the Lusi mud volcano, Indonesia - Tingay, Mark (SOC EXPLORATION GEOPHYSICISTS, 2015)
The Lusi mud volcano of East Java, Indonesia, remains one of the most unusual geologic disasters of modern times. Since its sudden birth in 2006, Lusi has erupted continuously, expelling more than 90 million cubic meters of mud that has displaced approximately 40,000 people. This study undertakes the first detailed analysis of the pore pressures immediately prior to the Lusi mud volcano eruption by compiling data from the adjacent (150 m away) Banjar Panji-1 wellbore and undertaking pore pressure prediction from carefully compiled petrophysical data. Wellbore fluid influxes indicate that sequences under Lusi are overpressured from only 350 m depth and follow an approximately lithostat-parallel pore pressure increase through Pleistocene clastic sequences (to 1870 m depth) with pore pressure gradients up to 17.2 MPa/km. Most unusually, fluid influxes, a major kick, connection gases, elevated background gases, and offset well data confirm that high-magnitude overpressures also exist in the Plio-Pleistocene volcanic sequences (1870 to approximately 2833 m depth) and Miocene (Tuban Formation) carbonates, with pore pressure gradients of 17.2-18.4 MPa/km. The varying geology under the Lusi mud volcano poses a number of challenges for determining overpressure origin and undertaking pore pressure prediction. Overpressures in the fine-grained and rapidly deposited Pleistocene clastics have a petrophysical signature typical of disequilibrium compaction and can be reliably predicted from sonic, resistivity, and drilling exponent data. However, it is difficult to establish the overpressure origin in the low-porosity volcanic sequences and Miocene carbonates. Similarly, the volcanics do not have any clear porosity anomaly, and thus pore pressures in these sequences are greatly underestimated by standard prediction methods. The analysis of preeruption pore pressures underneath the Lusi mud volcano is important for understanding the mechanics, triggering, and longevity of the eruption, as well as providing a valuable example of the unknowns and challenges associated with overpressures in nonclastic rocks.